Relationship between athlete stress and burnout: a systematic review and meta-analysis - Lin, C. H.; Lu, F. J.; Chen, T. W.; Hsu, Y. (International Journal of Sport and Exercise Psychology, 2022)
Burnout is a negative consequence of stress and has received attention in sports research. On the basis of Smith`s [(1986). Toward a cognitive-affective model of athletic burnout. Journal of Sport Psychology, 8(1), 36-50. https://doi.org/10.1123/jsp.8.1.36] cognitive-affective model of athlete burnout, we conducted this systematic review and meta-analysis to quantify the correlation between athlete stress and burnout. After searching academic databases for the 2001-2021 period, we selected 48 empirical studies for analysis, of which 44 used the Athletes Burnout Questionnaire with a three-dimension model to measure athlete burnout. The athlete stress measurement tools were considerably diverse, including the Perceived Stress Scale, the College Student-Athletes` Life Stress Scale, and the Recovery-Stress Questionnaire for Athletes. The meta-analysis results confirmed the stress-burnout correlation, yielding an overall effect size of 0.505. The r values for the correlation of athlete stress with overall burnout and the three dimensions of burnout ranged from 0.402-0.532. The correlation between stress and a reduced sense of accomplishment was highest among participants of all ages and competitive levels. Furthermore, the correlation between stress and devaluation of sports participation was relatively low in all groups. The results revealed differences in the stress-burnout correlation in different age groups. However, most of the included studies used student-athletes as research samples, which highlights the need for further research exploring the continuity of and change in the stress-burnout correlation across athletes` lives. The implications of the results are discussed herein.